Preparation of ionic liquid‐modified magnetic nanoparticles based on thiol‐ene click chemistry for the analysis of polycyclic aromatic hydrocarbons in water and smoked meat samples. Issue 7 (28th January 2019) - Lu, Junyu; Lu, Sufen; Yao, Dongmei; Huang, Xiuxiang; Lai, Hongfang; Yin, Xiuju
Abstract : In the present study, ionic liquid (IL)‐modified Fe3 O4 magnetic nanoparticles (Fe3 O4 ) were synthesized by the thiol‐ene click reaction for magnetic solid‐phase extraction (MSPE) of polycyclic aromatic hydrocarbons (PAHs) in water and smoked meat samples. An IL 1‐vinyl‐3‐butylimidazolium bromide was firstly synthesized, and then immobilized on the surface of thiol group‐functionalized Fe3 O4 via a thiol‐ene click reaction. The as‐synthesized Fe3 O4 @ILs were characterized using Fourier transform infrared spectroscopy, X‐ray diffraction, and transmission electron microscopy. Various parameters (including the amount of adsorbent, extraction time, sample volume, and desorption conditions) affecting MSPE were optimized. Under the optimum conditions, the limits of detection of four PAHs in the range of 0.6–7.2 ng/L were obtained using high‐performance liquid chromatography–ultraviolet detection. The accuracy of the method was assessed by recovery measurements on spiked real samples and good recovery of 80–108% with relative standard deviations lower than 8.16% was achieved. The enrichment factors ranging from 699 to 858 were obtained for the analytes. This result indicated that the proposed method had great potential for sample preparation. Abstract : A novel thiol‐ene click chemistry strategy for the preparation of IL‐modified Fe3 O4 magnetic nanoparticles was proposed, which were used as adsorbents for the enrichment of polycyclic aromatic hydrocarbons (PAHs) in water and smoked meat samples. The proposed method offered low limits of detection for PAHs in the range of 0.6–7.2 ng/L and high enrichment factors ranging from 699 to 858.